(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Midday Meal scheme is the first of its type and the most extensive feeding programme that has ever been initiated by the Government of India. Under the terms of this programme, a single lunch is provided to each and every child attending a government-run or governmentaided school or madrasa from the first to the eighth grade at least two hundred days out of each year. Preparation workshops for school lunches are planned to be implemented in elementary schools across Delhi-NCR as part of the NEP 2020’s school meal programme. The Mid-Day Meal Scheme plays a crucial role in the framework of the manifestation of the principles of NEP & Delhi govt. 2020, which are availability, Fairness, Quality, Cost, and Responsibility. The Delhi-NCR government has found that when children are malnourished or otherwise ill, they are unable to learn as effectively as they could. A significant number of children who come from impoverished parts of society enter puberty with an empty stomach. Even if they have breakfast before they head off to school, by the time lunch rolls around, youngsters are unable to concentrate because they are hungry. The "classroom hunger" that children experience can be alleviated with a meal at midday. According to the findings of a number of research investigations, when kids are hungry or sick, they can’t focus on schoolwork as much. As a result, the strategy mandates bringing highly qualified social workers, counsellors, plus community involvement into the educational system to improve students’ physical and mental health. This will be accomplished by providing children with nutritious meals. There are always certain problems lurking in the shadows behind every policy, and in order to address such problems effectively, it is necessary to investigate them in depth. Issues about the role, vision, expectations, and malpractices associated with the Midday Meal Scheme were discussed in this article. Also findings suggest that a greater number of students are now enrolled since free lunch became available. According to the results of the previous research, many parents are eager to enrol their children. Midday meals have been shown to boost retention by as much as 30%. The traditional leader has voiced approval of the school lunch programme and its potential benefits. Students from low-income families are more likely to attend school and enrol thanks to the Mid-Day Meals programme. The Midday Meals programme has widespread support among rural educators and village chiefs. It has been discovered that rural school principals are generally supportive of the idea of implementing a school-wide midday meal programme for elementary students.